Konstruksi Sosial Masyarakat Desa Craken Tentang Tradisi Longkangan di Kabupaten Trenggalek - Herbiyanto, Dimas Gadang (Paradigma, 2022)
This paper discusses the social construction of the Craken village community regarding the longkangan tradition in Trenggalek Regency. This study uses the theoretical concept of Peter L. Berger with three components, namely externalization, objectivation and internalization. This study uses qualitative methods and uses a phenomenological approach with the aim of uncovering a phenomenon of cultural behavior that occurs in the Craken village community. The research location is in Craken Village, Trenggalek Regency. The results of the research regarding the construction of the Craken village community regarding the longkangan tradition, namely the first, the Longkangan tradition as a sacred culture. Second, the longkan tradition as a means of asking for safety and thanksgiving. Third, the longkan tradition as an investment for the future. Fourth, the longkan tradition as a means of communication and social interaction. Fifth, the tradition of longkan as entertainment every year. Keywords: Social Construction; Longkan; Public; Tradition.